Psychological Effects of Policy on Writing Off and Rescheduling of Credit Arrears on Members of Non-Governmental Organizations (KSM) (Case Study in P2KP-PNPM Mandiri Gempol Village, Gempol District, Pasuruan Regency) - Mas Drajat (Universitas Muhammadiyah Sidoarjo, 2011)
The reality in early 2001, after the P2KP-PNPM Mandiri program was implemented to alleviate poverty, there was a revolving business capital for the poor, but after several years in line with that, many credit arrears appeared in non-governmental groups as a result this program did not run optimally, to overcome With this obstacle, the government issued a policy of writing off and rescheduling credit arrears to members of non-governmental groups (KSM). This study uses a descriptive qualitative research type that is casuistic in nature while the approach used in this study is an inductive approach, this research was conducted at P2KP-PNPM Mandiri Gempol Village, Gempol District, Pasuruan Regency. Determination of research subjects using purposive random sampling technique by following the principle of snowball, data collection using documentary methods, in-depth interviews and participatory observation. Examination of the data used source triangulation techniques and method triangulation techniques while data analysis was carried out through three channels, namely data reduction, data presentation and conclusion drawing/verification. The analysis techniques used were content analysis and thematic analysis. Findings in the field explain that the policy of writing off and rescheduling credit arrears has had a psychological effect on members of Non-Governmental Organizations (KSM). This is because the average KSM member is a poor community whose economic conditions are uncertain. Loan arrears that have not been repaid for a long time can also be caused by various factors including individual personality, cultural, social, religious, and so on. The factors above have made various psychological effects that arise among KSM members which can be seen from the point of view of the cognitive dimension (individual perception, individual opinion, and individual awareness), affective dimension (individual feelings, individual emotional, and individual motivation) and dimensions of conation (attitudes, expressions, individual behavior, individual social interaction dynamics, and individual communication patterns). The psychological effect of the write-off policy on credit arrears is seen from the cognitive dimension; the aspect of individual perception is that because of the grant money, they assume that even if it is not returned there is no problem, the aspect of individual opinion is the tendency to agree and agree, the aspect of individual awareness is discipline, low responsibility and even demoralization appears. The affective dimension: the individual feeling aspect is the tendency to feel happy, the individual emotional aspect is the emotional tendency to be uncontrollable, excessive even though they know responsibility, the individual motivation aspect is life experience, the spirit to organize life back to the front because it is not burdened. Dimensions of conation: aspects of individual attitudes, expressions and behavior are the tendency to surrender and don't want to try, and compromise, aspects of the dynamics of individual social interactions are lack of socializing with society, individualistic and shy, aspects of individual communication patterns are defense tendencies towards problems. The psychological effect of rescheduling credit arrears is seen from the cognitive dimension: the individual perception aspect is the tendency to become a burden in the future, the individual opinion aspect is the tendency to disagree and disagree, the individual awareness aspect is discipline, low responsibility. The affective dimension: the individual feeling aspect is the tendency to feel unhappy, the individual emotional aspect is the tendency to feel depressed and restless and even pretend to forget the credit arrears they have, the individual motivation aspect is the desire to return even though they are forced to. Dimensions of conation: aspects of individual attitudes, expressions, and behavior are the tendency to belittle, reluctant to reverse, burdened, depressed, and there is no belief in being responsible, the dynamic aspect of individual social interactions is lack of socializing with society, individualistic, aspects of individual communication patterns are tendencies closed and defended his own ego.